KEPEMIMPINAN TRANSFORMATIF DI MADRASAH MINORITAS MUSLIM PAPUA BARAT - Wekke, Ismail Suardi; Rubawati, Efa; Nurjannah, Siti (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
Madrasah as the oldest institution, constantly have to innovate for the sake of maintaining the quality of education. To meet the leadership of the madrasa has a shareÂ fully in developing and advancing the whole element of education, ranging from human resources to management. This research was descriptive qualitative approach to theÂ leadership of Madsarah Ibtidaiyah Roudlotul Khuffadz of West Papua in extending the educational system through the transformative leadership patterns that are very dynamic and democratic, developing human resources simultaneously, process leadership (planning, organizing, moving and cordinatoring), encourages the occurrenceof sincere work. Finally, other efforts are implemented memorizing the Qur'an, mapping the talents of interest of students, evaluation of each program and pay attention to accountability and transparency.